Strategies and methodological basics for prevention of sexually transmitted infections in the high-risk subpopulations - T. V. Krasnoselskikh; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
A review article presents theoretical basics of the development of innovative STI prevention programs for high-risk groups Urgent need for integrated multidisciplinary preventive strategies aimed at correcting risky behaviors and adapted for the particular vulnerable populations is justified.